Enhanced DBCC for high-speed permanent magnet synchronous motor drives - Tang, M.; Gaeta, Alberto; Formentini, Andrea; Ohyama, K.; Zanchetta, Pericle; Asher, Greg (IET, 2016)
High bandwidth and accuracy of the current control loop are fundamental requisites when a fast torque response is required or for facilitating the reduction of torque ripple in high performance drives, especially at high speed. One of the most suitable control methods to achieve these goals is dead beat current control (DBCC). Many types of DBCC have been proposed and implemented in literature. This paper proposes a DBCC incorporating two new functionalities. One is a two steps current prediction to improve prediction accuracy when current measurements are taken place before each sampling period; and particularly to reduce the overshoot during transients when mean value is used as current feedback. The second is a novel compensation method for the rotor movement to eliminate offset errors which occur at high speed. Moreover, the dynamic and steady state performance of the proposed DBCC is assessed in simulations. On the basis of the simulation tests, the control parameters are tuned for experiments and the performance of the proposed functionalities are verified. Finally, the advantage of DBCC, compared with a classical dq PI current regulator, is verified in experiments.